Effect of non-contact induction heating on HA coatings and bone cement, an ex vivo study [version 2; peer review: 2 approved, 1 approved with reservations] - Robert Kamphof; Dr. Bart G.C.W. Pijls; Dr. Rob G.H.H. Nelissen; Jeroen Mesman-Vergeer; Dr. Giuseppe Cama (F1000Research)
Background Prosthetic joint infection is a serious complication that can arise after total joint replacement surgery. When bacteria colonise an orthopaedic implant, they form biofilms that protect them from their environment, making them difficult to remove. Treatment is further complicated by a global rise of antimicrobial resistance. These protective mechanisms make treatment of prosthetic joint infection increasingly complex. Non-contact induction heating is an upcoming technology that uses heat to eradicate bacteria that are present on the surface of metallic implants. This study aims to provide insight into the feasibility of using non-contact induction heating on metallic implants that are in direct contact with other biomaterials, such as coatings composed of hydroxyapatite and bone cement composed of poly (methyl methacrylate) (PMMA). Methods Characterisation of hydroxyapatite coatings and adhesion strength tests were conducted according to standards set by the International Organisation for Standardisation (ISO 13779-2). The fixation strength of acrylic bone cement was tested according to an adapted method from ISO. Results It was found that non-contact induction heating did not significantly affect the adhesion strength of hydroxyapatite coatings. In contrast to hydroxyapatite coatings, acrylic bone cement softened temporarily as the temperature exceeded the glass transition temperature (83.38 ± 10.88°C). However, the induction heating temperature had no significant effect on the fixation strength after the cement was allowed to cool down. Conclusion This study shows the feasibility of using non-contact induction heating up to 80°C when bone cement or ceramic coatings are present in contact with infected metallic implants.